PENGARUH MARKETPLACE, PRICING, KUALITAS DAN INOVASI PRODUK TERHADAP PENINGKATAN PENDAPATAN UMKM SURABAYA PASCA PANDEMI COVID-19 - Farah Putri Ariatama; Rokhmania, Nur'aini (Jurnal Bisnis Terapan, 2025)
The COVID-19 pandemic has shaken the economies of almost all countries, including Indonesia. The use of marketplace technology is one way to make MSMEs survive, especially during a pandemic that requires all activities to take place online or without face-to-face contact. This study aims to determine the effect of marketplace, pricing, quality and product innovation on increasing MSME income in the Surabaya Region after the COVID-19 pandemic. The method used in this research is quantitative with primary data. The sampling technique was carried out using purposive sampling technique so that the results obtained were more relevant to the research title. The sample obtained was 104 respondents in accordance with the research criteria. Researchers used the help of WarpPLS version 8.0 software using the PLS-SEM model. The research results show that Marketplace has an impact on increasing MSME income, but pricing, quality, and product innovation do not have an impact or no effect.